2009
DOI: 10.1088/0029-5515/49/8/085035
|View full text |Cite
|
Sign up to set email alerts
|

Pedestal stability comparison and ITER pedestal prediction

Abstract: The pressure at the top of the edge transport barrier (or "pedestal height") strongly impacts fusion performance, while large Edge Localized Modes (ELMs), driven by the free energy in the pedestal region, can constrain material lifetimes. Accurately predicting the pedestal height and ELM behavior in ITER is an essential element of prediction and optimization of fusion performance. Investigation of intermediate wavelength MHD modes (or "peeling-ballooning" modes) has led to improved understanding of important c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
244
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(284 citation statements)
references
References 40 publications
20
244
2
1
Order By: Relevance
“…I-mode pedestal data are compared to predictions based on kineticballooning mode (KBM) turbulence (section V), which is thought to set a strong constraint on the pedestal in ELMy H-modes [26][27][28]. I-mode pedestal widths are observed to have no trend with β p,ped , in contrast to the ∆ ψ ∝ β 1/2 p,ped scaling predicted from KBM physics, and are generally wider than predicted based on KBM-limited physics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…I-mode pedestal data are compared to predictions based on kineticballooning mode (KBM) turbulence (section V), which is thought to set a strong constraint on the pedestal in ELMy H-modes [26][27][28]. I-mode pedestal widths are observed to have no trend with β p,ped , in contrast to the ∆ ψ ∝ β 1/2 p,ped scaling predicted from KBM physics, and are generally wider than predicted based on KBM-limited physics.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed numerical studies of the MHD instabilities associated with ELM drive are accomplished through the ELITE code [30,47]. This method is also used for the MHD stability component of the predictive EPED model [26][27][28]. MHD stability modeling has been successfully applied on C-Mod in ELMy [33] and EDA [34] H-modes, and in extensive cross-machine H-mode studies [25].…”
Section: Mhd Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…EPEDE1 [3] It is important to notice that EPEDE1's prediction of the ITER pedestal profile is steeper than the profile we use in our analysis. DIII-D experiments [4] have already demonstrated that externally imposed stochastic magnetic fields could eliminate ELMs by keeping the pedestal stable against the peeling-ballooning instabilities.…”
mentioning
confidence: 85%
“…These are ideal MHD modes described by J' (current density gradient) and p' (pressure gradient). The stability boundary in this case is a line in the corresponding 2D plane [3]. Microtearing instability involves kinetic effects; the mode is primarily driven by the temperature gradient T'.…”
mentioning
confidence: 94%